(untitled) (Perspectivas em Ciência da Informação, 2009)
This article discusses the learning environments in the era of hypermedia and the Distance Education. For this, contextualizes the issue of technology and its impact on education. Presents the insertion of hypermedia and its applicability in this scenario and describes the hipermediatics environments, functions and correlations in the processes of instructional design. Make a contemporary reflection on the distance education, basically realizing the integration of technologies and languages and their connections with the field of learning.